Adaptation of the UTAUT model - Customers influence on technology adoption - Ebrahim, Rishaad; Naicker, Prof Visvanathaan (Archives of Business Research, 2019)
The role of technology adoption has become more important within SMEs for both their strategies and future sustainability. It’s important that SMEs are able to effectively deal with their business partners, be they suppliers or customers. The study considered the influence of competitive forces on SME technology adoption in developing economies, with a focus on customers. The primary objective of this study was to develop a working framework that will include the influence of competitive forces on SME technology adoption. An independent research organisation conducted 12 interviews with various SMEs, and thereafter conducted a survey which involved 214 SMEs around South Africa. A mixed method exploratory research was conducted. The Unified Theory of Acceptance and Use of Technology model was used as a baseline for the study. The findings have shown that technology adoption, in relation to competitive forces, is linked to Age, Experience and Voluntariness of Use. The findings suggest that the new Combined UTAUT model is vital when dealing with technology adoption. The UTAUT model was adapted and is now dedicated to SMEs in developing economies, which highlights the influence that customers have on SME technology adoption. The emphasis on customers has not been emphasised in previous technology acceptance models.